The Role of Accounting Knowledge in Supply Chain Risks Mitigation and Efficiency Improvement - Dabaghia, Mohammed Nadem (ExcelingTech, 2019)
Risk has penetrated in every aspect of life; no one can escape from it. It can disrupt not only the organization but whole system. It has become essential to mitigate the risks from each and every part of the system. Financial risks are considered more dangerous for the organization. This research aims to highlight the most important accounting knowledge that is forming the key of the auditing process, and how the auditors can modernize this knowledge. In order to access these objectives, the researcher conducted a telephone survey with 64 Jordanian auditors. The main results of this research revealed that; accounting knowledge is very important for the auditing process because it helps the auditor to discover any fraud in the financial transactions and statements, therefore modernizing the accounting knowledge becomes from the priorities of attention of the auditor and disclosure of financial statements that reflect validity and credibility increases stakeholder's satisfaction. According to these results, the researcher recommends that training courses that allow them to exchange their experiences, auditors should focus on manipulation through accruals and allowances and auditors should discuss their observations with the internal audit committee in the company. This study is conducted to only limit industry with few interviews only, to generalize the findings of this study, it is recommended to conduct the quantitative research with more respondents.